The Performance of IPOs on Small and Medium Enterprises Board and ChiNext - LIU, XUYANG (2011)
ABSTRACT This study examines and comparatively analyzes the underpricing and long-term performance of IPOs on the Chinese newly-established ChiNext market and Small and Medium Enterprises Board (SMEB) market, from the beginning of the ChiNext market on 30th Oct 2009 up to 15th Feb 2011, and includes 178 and 244 IPOs on ChiNext and SMEB, respectively. By doing so, a set of hypotheses dealing with the associations between IPOs performance and five categories of independent variables were examined. The five blocks of independent variables are signaling of firm quality, underwriter reputation, ex-ante and ex-post uncertainty surrounding IPO, corporate governance, industry effect and market conditions.